Cognitive and social congruence in peer-assisted learning - A scoping review. - Teresa Loda; Rebecca Erschens; Hannah Loenneker; Katharina E Keifenheim; Christoph Nikendei; Florian Junne; Stephan Zipfel; Anne Herrmann-Werner (PLoS ONE)
This scoping review presents an overview of cognitive and social congruence in peer assisted learning (PAL), as the positive effects of PAL have been shown to rely on these critical factors. The scoping review followed the guidelines of the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement. Databases were systematically searched for articles that focus on PAL and cognitive and social congruence. Participants of the studies included were medical, health science, polytechnic, law and paramedic students. Studies that assessed cognitive and social congruence by questionnaires with a 5-point Likert scale were regarded for meta-analytic pooling. Sixteen of 786 identified articles were included in the review, whereof 9 studies were considered for meta-analytic pooling. The meta-analytic pooling showed that tutees tend to see their student tutors as cognitively (Mweighted = 3.84; range of Mweighted = 2.69-4.56) and socially congruent (Mweighted = 3.95; range of Mweighted = 2.33-4.57). Further, characteristics of student tutors are summarized. This scoping review presents an overview and operationalization of cognitive and social congruence in PAL. Based on the presented meta-analytic pooling, cognitive and social congruence were found to represent relevant key factors in the PAL context. Thus, this theoretical background should be acknowledged as a core concept for tutorials within the medical curriculum.